AB0472 Predicting Factors Associated with Sustained Clinical Remission by Abatacept are Different Between in Younger and Elderly Patients with Biologic-Naïve Rheumatoid Arthritis (Abroad Study). (9th June 2015) - Sekiguchi, M.; Fujii, T.; Kitano, M.; Matsui, K.; Hashimoto, H.; Yokota, A.; Miki, K.; Yamamoto, A.; Fujimoto, T.; Hidaka, T.; Shimmyo, N.; Maeda, K.; et al.
Abstract : Background: Sustained clinical remission is crucial in the treatment of rheumatoid arthritis (RA). However, baseline predicting factors to achieve sustained clinical remission in RA patients treated with abatacept (ABT) are little known. Objectives: The ABROAD (ABbatacept Research Outcomes as a first-line biological Agent in the real worlD) study is the prospective multicenter observational cohort study, in which 44 institutions in the west side of Japan participate to investigate both efficacy and safety of ABT in biologic-naïve RA patients. The purpose of the present study was to determine the useful markers associated with sustained clinical remission by the intravenous ABT infusion treatment in different age groups (age ≥65 vs <65 years old). Methods: Two-hundred and seventy-seven RA patients with high or moderate disease activity (female =84.8%, mean age at the ABT initiation =63.2 years old, disease duration =7.9 years) were enrolled. Disease Activity Score 28 joint based on C- reactive protein (DAS28-CRP) remission rate at 24, 36, and 48 weeks after the initiation of ABT treatment were examined. Then, patient profiles, disease activity, concomitant drug use, and laboratory findings at baseline associated with sustained clinical remission (>12 weeks) during the last 24 weeks in the whole treatment period (48 weeks) were determined by logistic regression analysis. Results: The proportion of patients, who achieved DAS28-CRP-defined clinical remission at 24 and 48 weeks, were 35.1% and 36.5% in elderly patients (≥65 years old) and 34.9% and 43.4% in younger patients (<65 years old), respectively. In elderly patients, anti-citrullinated protein antibody (ACPA) positivity (Odds ratio [OR] =6.56, 95% confidence interval [CI] =1.34-50.39, p=0.017) and moderate disease activity (MDA, DAS28-CRP<4.1) at baseline (OR =4.23, 95% CI =1.75-10.83, p=0.001) were significantly associated with sustained clinical remission. In younger patients, however, concomitant MTX use (OR =5.09, 95% CI =1.42-24.71, p=0.011) and HAQ-DI score≤0.75 at baseline (OR =6.19, 95% CI =2.66-15.36, p<0.0001) were the predictive factors for sustained clinical remission. Conclusions: The efficacy of ABT in biologic-naïve RA patients was equivalent between younger and elderly patient groups, while the baseline clinical characteristics in association with clinical remission were totally different. ACPA positivity or MDA at baseline in elderly, but concomitant MTX use or lower HAQ score at baseline in younger patients, may be the useful predicting factors for achieving sustained clinical remission by ABT. Disclosure of Interest: M. Sekiguchi Grant/research support from: Bristol-Myers K.K., T. Fujii Grant/research support from: Bristol-Myers K.K., M. Kitano Grant/research support from: Bristol-Myers K.K., K. Matsui Grant/research support from: Bristol-Myers K.K., H. Hashimoto: None declared, A. Yokota: None declared, K. Miki: None declared, A. Yamamoto Grant/research support from: Bristol-Myers K.K., T. Fujimoto: None declared, T. Hidaka: None declared, N. Shimmyo: None declared, K. Maeda: None declared, T. Kuroiwa: None declared, I. Yoshii: None declared, K. Murakami Grant/research support from: Bristol-Myers K.K., K. Ohmura Grant/research support from: Bristol-Myers K.K., S. Morita: None declared, Y. Kawahito Grant/research support from: Bristol-Myers K.K., N. Nishimoto: None declared, T. Mimori Grant/research support from: Bristol-Myers K.K., H. Sano Grant/research support from: Bristol-Myers K.K.